Analisis Kontribusi Retribusi Pasar terhadap Pendapatan Asli Daerah (PAD) Kabupaten Toraja Utara - Trisnawanti Lamba’; Olivia Devi Yulian Pompeng; Lisa Kuniasari Wibisono (Universitas Kristen Indonesia Toraja, 2025)
Local Revenue (PAD) refers to the income obtained by regional governments from sources within their own jurisdiction, such as taxes and local levies. One of the important components of PAD is market levies, which are collected from traders as a fee for the use of market facilities. This study aims to analyze the contribution of market levies to PAD in North Toraja Regency. The method used in this study is descriptive quantitative, utilizing secondary data from the Bapenda of North Toraja for the period of 2020–2024. The results of the study show that the contribution of market levies to PAD fluctuates with a downward trend. In 2020, the contribution was recorded at 1.17%, but by 2024, it decreased to 0.71%. This decline is attributed to several factors, including increased competition from modern markets that are more attractive to consumers, a decrease in the number of buyers visiting traditional markets, and arrears from traders, which has led to suboptimal revenue collection from levies. These findings highlight the importance of efforts by local governments to enhance the appeal of traditional markets and manage levies more effectively in order to increase their contribution to PAD in the future.